UPAYA PENANGGULANGAN KEMISKINAN MELALUI PENDEKATAN PROSES (STUDI KASUS MASYARAKAT WUDI NUSA TENGGARA TIMUR) - Ubur, Hubertus (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2011)
This paper aims to address the subject matter, “Why does poverty still exist, while many theoretical and practical efforts put forward to the direction of the solution?.” In connection with the subject matter, the author describes some of the theories of poverty and some examples of poverty reduction. One practical example is taken from the results of field research on community Wudi, West Flores. The authors propose an alternative notion of a process approach in solving the poverty problem. The process approach consists of two things: 1) Active involvement of the poor in the assessment, planning, implementation and evaluation of poverty reduction programs; and 2) Sustainability of a poverty reduction program. Approach made the process so that poverty reduction programs not only shaped “project” alone, so it does not seem as activities just to spend the budget you have available. Philosophical basis of this approach is the concept of man which is a ‘creature is not at all be a’ but ‘a creature that continues to be’.